2008
DOI: 10.1111/j.1399-3054.2008.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of potassium transport in plants

Dev T. Britto,
Herbert J. Kronzucker

Abstract: Potassium (K(+)) is the most abundant ion in the plant cell and is required for a wide array of functions, ranging from the maintenance of electrical potential gradients across cell membranes, to the generation of turgor, to the activation of numerous enzymes. The majority of these functions depend more or less directly upon the activities and regulation of membrane-bound K(+) transport proteins, operating over a wide range of K(+) concentrations. Here, we review the physiological aspects of potassium transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(145 citation statements)
references
References 159 publications
(194 reference statements)
2
141
0
2
Order By: Relevance
“…While the maintenance of a high K + /Na + activity ratio in the cytosol of plant root cells is frequently described in the literature as being a critical determinant of plant performance under salinity stress, direct evidence supporting this contention is, by comparison, extremely rare. While there is a strong consensus from independent lines of evidence that the cytosolic levels of K + in plant cells are typically around 100 mM Britto and Kronzucker 2008), measurements of cytosolic Na + differ dramatically from one another, depending on the methods used . This can be illustrated by comparing two studies examining the same pair of barley cultivars, one using X-ray microanalysis , the other using intracellular Na + -specific electrodes (Carden et al 2003); estimates from the two studies disagree from 4-to 90-fold (although it should be noted that different exposure times to elevated NaCl were used).…”
Section: Osmotic and Ionic Effects: What Is The Difference?mentioning
confidence: 99%
“…While the maintenance of a high K + /Na + activity ratio in the cytosol of plant root cells is frequently described in the literature as being a critical determinant of plant performance under salinity stress, direct evidence supporting this contention is, by comparison, extremely rare. While there is a strong consensus from independent lines of evidence that the cytosolic levels of K + in plant cells are typically around 100 mM Britto and Kronzucker 2008), measurements of cytosolic Na + differ dramatically from one another, depending on the methods used . This can be illustrated by comparing two studies examining the same pair of barley cultivars, one using X-ray microanalysis , the other using intracellular Na + -specific electrodes (Carden et al 2003); estimates from the two studies disagree from 4-to 90-fold (although it should be noted that different exposure times to elevated NaCl were used).…”
Section: Osmotic and Ionic Effects: What Is The Difference?mentioning
confidence: 99%
“…Genetic modification of Pi transport proteins are maybe the key in developing tolerance to both -P and ++P stress. Britto and Kronzucker (2008) reported that the high-affinity transport system is strongly downregulated under K + -replete conditions and is conversely strongly upregulated under K + -starvation conditions and that the LATS (low-affinity transport system)-range K + influx may be increased generally by increased K + (Britto and Kronzucker. 2008).…”
Section: Identification Of Responsive Non-protein Coding Transcripts mentioning
confidence: 99%
“…The organic acid contents in root exudates were determined by HPLC Agilent 1100 and DAD detector with wavelength of 210 nm. Root excretion H + was determined using the method as described by Britto and Kronzucker (2008):…”
Section: Chemical Analysis and Parameter Calculationmentioning
confidence: 99%